The new reconstruction technique in the treatment of the skin cancers located on the eyelid: Posterior temporalis fascia composite graft - Copcu, Eray (BioMed Central, 2004)
BACKGROUND: Difficulty of reconstruction of the eyelids arises from the need to reconstruct different supporting and covering structures in a single operation. Defects in the anterior lamella of the eyelids can be readily repaired with skin grafts or flaps but posterior lamellar reconstruction needs more complex applications. METHODS: We performed posterior lamellar eyelid reconstruction with posterior parts of the temporalis fascia, since their anatomical and histological features are very similar to the defects. Nine patients with skin tumors located on the periorbital region were treated with local skin flaps and deep layer of the temporalis fascia. RESULTS: Grafts were harvested very easily. There was no complication related with graft or donor site. Biopsy was performed in three cases and normal conjunctival elements were seen. Functional and acceptable aesthetically results were achieved in all patients. CONCLUSION: Ideal reconstructive material for replacement of the posterior lamina is still lacking. Tarsal reconstruction can be made with deep temporalis fascia with success since the thickness of the both tissues are very similar and also since the loose areolar layer of the temporalis fascia is very thin and highly vascularized, this layer can be used in reconstruction of the conjunctiva. According to our knowledge this is the first report of using of the posterior part of temporalis fascia as a composite graft in the literature.